Implementation Of The Pancasila Student Profile Strengthening Project (P5) As An Effort To Strengthen The Character Of Students - Susanti Susanti; Muaza Muaza; Supian Supian (Jurnal Indonesia Sosial Teknologi, 2023)
21st-century education in Indonesia faces significant challenges, especially in preparing the younger generation to face advances in information and communication technology. 21st-century skills, consisting of critical thinking, creativity, cooperation, communication, culture, and connectivity, are becoming the key to success in the world of work and social life. However, data such as Indonesia's low ranking in international studies such as PISA and TIMSS point to an urgent need to improve the education system. The achievement of perfection in the quality of life is the ultimate goal of education. This research uses qualitative methods with literature studies as the main approach. The implementation of character education in the school environment is the focus, involving planning, implementation, and evaluation. Various definitions and expert views on implementation are used to understand this process. The character development of students in the Strengthening the Profile of Pancasila Students project is the main key, not only the implementation of fun activities but also the formation of strong character. This process engages learners to the maximum, allowing them to grow into responsible and positively contributing individuals. Reflection becomes an important part of every activity, helping to identify strengths and weaknesses and determine next actions. This journal presents an in-depth understanding of the challenges and efforts in improving education in Indonesia, focusing on the character-building of students and the implementation of Pancasila values in the educational process